Upaya Merekonstruksi Pemahaman Simbol Swastika oleh The Hindu Forum of Britain - Nikki Avalokitesvari, Ni Nyoman Ayu; Fasisaka, Idin; Parameswari, A.A Ayu intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRACT This research examines the effort of the Hindu Forum of Britain on reconstructing the comprehension meaning of the Swastika symbol in Europe. This topic is noteworthy to be researched remembering that the position of the discourse about Swastika meaning according to Hinduism in Europe still become other discourse, indeed almost discriminated by the incoming plan of Swastika symbol banning all over the Europe. It happened because the European people associating the Swastika symbol with the non-humanist action which done by the Nazi in the World War II period. Whereas according to Hinduism, Swastika symbol is a symbol that representing luck, prosperity, happiness, protection, and so many other positive meaning. There are some concepts that used in this research such as; concept meaning in international relation, concept of strategic action, and concept of discursive struggle. Result of this research exhibit that on its history, Swastika is a symbol that have a positive meaning and already used by various culture around the world far before Nazi used it as one of their main identity. Swastika distribution which founded in various countries had an identic meaning with the swastika on Vedic civilization in India. Responding to the onset of prohibition efforts, there are some efforts made by the Hindu Forum of Britain as a form of strategic actions to reconstruct the Swastika symbol comprehension in Europe. Keywords : Swastika, The Hindu Forum of Britain, Strategic Action, Discursive Struggle